Basics of project planning and analysis: Project identification, formulation and appraisal - Rwechungura, F. A (Mzumbe University, 2025)
Preface. Project planning and Analysis is a book that focuses on the methodology or approach of planning and analyzing a project from the perspectives of the owners or funders of the project. The core philosophical base for this book comes from my conviction that, in this country and many other developing countries, university students (under/postgraduates) find it difficult to access the most new and up-to-date reading resources not only in this field but also in other fields as well. Although this book is not a complete substitute for recommended text books for the course, still it is a standalone reading and reference material in the sense that it is a concise and comprehensive account of what any student undertaking this course is supposed to learn. Again the book has been authored in a style that is user friendly even for field workers/practitioners (i.e. the book can be used both as a reference material for students and as a planning guide for practitioners). In order to achieve this goal I have used many diagrams, Boxes, examples and solved self-test questions so as to be able to clearly communicate difficult concepts; and areas covered in this book follow a 'simple to complex' approach in terms of their discussion. The approach I prefer most in my teaching.